Novel photopolymerizable high-refraction monomer with high sulfur content and preparation method of novel photopolymerizable high-refraction monomer

By introducing dithioheteropentanyl groups into the molecular structure of optical materials, a high sulfur content photopolymerizable high refractive monomer was designed, which solved the problems of low refractive index and unsatisfactory comprehensive performance of existing optical materials, and achieved high refractive index and environmentally friendly material preparation.

CN119528894AActive Publication Date: 2025-02-28JIANGSU JICUI PHOTOSENSITIVE ELECTRONIC MATERIAL RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411483973.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-28
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing optical materials are mainly acrylate monomers with low refractive structures, with high viscosity, low refractive index, and unsatisfactory comprehensive performance, which limits the application range of the material.

Method used

Introducing dithioheteropentane groups to the molecular structure, a new high-sulfur-contained photopolymerizable high-refractive monomer was designed, and a monomer with high refractive index was formed by reacting with compounds such as epoxychlorohydrin, NH4SCN, sodium hydrosulfide, hydrogen sulfide and dihydroxydithianes.

Benefits of technology

It achieves a high refractive index of the material (refractive index above 1.668), while ensuring that the monomer is liquid, no solvent is required during the polymerization process, environmentally friendly and low production cost, and is suitable for micro-nano structure manufacturing fields such as electronic packaging glue, optical devices, and printed circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098240120000011
    Figure BDA0005098240120000011
  • Figure BDA0005098240120000021
    Figure BDA0005098240120000021
  • Figure BDA0005098240120000031
    Figure BDA0005098240120000031
Patent Text Reader

Abstract

The invention relates to the technical field of organic chemistry, in particular to a novel high-sulfur-content photopolymerizable high-refraction monomer and a preparation method thereof.The series of high-refraction structures are not reported in literatures at present, dithiocyclopentane serves as a connecting unit and is combined with a series of structural units with the high molar refractive index and photocurable groups, and the novel high-sulfur-content photopolymerizable high-refraction monomer is obtained. The refractive index of the material is improved, the monomer is ensured to be in a liquid state, and the monomer is easy to dissolve, full-solid and pollution-free in the polymerization process; the structure contains rigid large conjugated aromatic rings and high-sulfur content dithiocyclopentane methyl mercaptan, so that the dispersion of the material is reduced, and meanwhile, certain physical properties are endowed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic chemistry, and in particular to a novel high-sulfur-content photopolymerizable high-refractive monomer and a preparation method thereof. Background Art

[0002] Optical resins are becoming more and more popular due to their light weight, impact resistance, easy processing, dyeability and excellent optical properties. They are gradually replacing inorganic optical materials and are widely used in the manufacturing fields of optical fiber communication materials, LED packaging, resin lenses, precision lenses and functional coatings. The continued development of these optical devices is closely related to the development of high refractive index (RI) materials. The higher the refractive index, the thinner the material is to achieve the same display effect. Functional materials with higher refractive index are more suitable for the manufacture of advanced optical devices. However, the molding method of high refractive index resins is mainly thermal curing, which has slow molding, high energy consumption and environmental problems. Photocuring allows materials to be quickly cured and molded under light, with the advantages of high efficiency, precision, environmental protection and energy saving. However, the optical materials widely used in the market are mainly acrylic monomers with low refractive structure, which have high viscosity, low refractive index and unsatisfactory comprehensive performance, which limits the application range of the materials. In view of the limitations of the prior art, the present invention introduces a dithiolane group into the molecular structure, which increases the refractive index of the material and makes the monomer liquid, thereby avoiding the use of solvents during the polymerization process. It is environmentally friendly and has low production costs, and can well make up for the defects of traditional acrylate monomers, so that it has good application prospects in the fields of micro-nano structure manufacturing such as electronic packaging adhesives, optical devices, and printed circuits. Summary of the invention

[0003] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art: to provide a novel high-sulfur-content photopolymerizable high-refractive monomer and a preparation method thereof.

[0004] In order to solve the above problems, the technical solution provided by the present invention is as follows:

[0005] A new type of high-sulfur-content photopolymerizable high-refractive monomer, the structural formula is as follows:

[0006]

[0007] in,

[0008] R1 is selected from -H, -CH3,

[0009] R2 is selected from

[0010] Preferably, the method comprises the following steps:

[0011] (1) using SH-R2-SH thiol compound as raw material to react with epichlorohydrin to form an epoxy group compound, and then reacting with NH4SCN to undergo an episulfide reaction to obtain an episulfide group compound;

[0012] (2) reacting the epithio group compound with sodium hydrosulfide and hydrogen sulfide to obtain two dithiol group compounds;

[0013] (3) reacting the product of step 2 with dihydroxydithiane to obtain a dithiolane methylthiol group compound;

[0014] (4) the product of step 3 is substituted with (meth)acrylic anhydride under base catalysis to prepare a corresponding high refractive monomer;

[0015] The reaction formula is as follows:

[0016]

[0017] Preferably, the molar ratio of the thiol compound with hydrogen connected to both ends of the R2 substituent in step 1 to epichlorohydrin is 1:2-10; and the molar ratio of the epoxy group compound to NH4SCN in the episulfide reaction is 1:2-8.

[0018] Preferably, the reaction temperature for forming the epoxy group compound in step 1 is -120°C, and the episulfide reaction temperature is room temperature.

[0019] Preferably, the molar ratio of the episulfide compound to sodium hydrosulfide and hydrogen sulfide in step 2 is 1:1.5-3:2-5.

[0020] Preferably, the reaction temperature in step 2 is 0-5°C.

[0021] Preferably, in step 3, the molar ratio of the product of step 2 to dihydroxydithiane is: 1:compound 1-2.

[0022] Preferably, the reaction temperature in step 3 is from room temperature to reflux heating.

[0023] Preferably, in step 4, the molar ratio of the product of step 3 to (meth)acrylic anhydride is 1:2-3, the base is triethylamine or 4-(N,N-dimethylamino)pyridine, and the molar ratio of the product of step 3 to the base is 1:2-5.

[0024] Preferably, the reaction temperature in step 4 is 15-100°C.

[0025] The specific structure of the present invention is exemplified as follows:

[0026]

[0027] The beneficial effect of the present invention is that a series of high-refractive monomer structures with high sulfur content are designed. The refractive index performance of the compound is characterized by using an Abbe refractometer, and the values ​​are all above 1.668, and can be used for the preparation of high-refractive devices. It has a wide spectral range, high chemical stability, and good adjustability. It has a wide range of application potential in different fields such as high-refractive lenses, optical fibers and other optical components, ultraviolet, visible and near-infrared optical devices, optical communication systems such as lasers and optical fiber sensors, chemical and biological sensors, photoresists, coatings, etc. There is no literature report on this series of high-refractive structures. In addition, the synthesis route of the present invention has universality, with dithiocyclopentane as a connecting unit, combined with a series of structural units with high molar refractive index and photocurable groups, while improving the refractive index of the material, the monomer is ensured to be in a liquid state, and the polymerization process can be easily soluble, fully solid-containing, and pollution-free; the structure contains a rigid large conjugated aromatic ring and dithiocyclopentane methyl mercaptan with a high sulfur content, which reduces the dispersion of the material and gives certain physical properties. DETAILED DESCRIPTION

[0028] The present invention is described below with reference to examples, but the present invention is not limited thereto. In the art, simple replacement or improvement made by technicians in the field to the present invention belongs to the technical solution protected by the present invention.

[0029] Example 1 Preparation of Compound 1

[0030] The reaction formula for preparing compound 1 is as follows:

[0031]

[0032] Wherein, the synthesis process of compound 1-ii is as follows:

[0033] In a four-necked bottle equipped with a stirring blade, a thermometer, a constant pressure dropping funnel, a serpentine condenser and a nitrogen protection device, compound 1-i (100g, 0.357mol) and tetramethylammonium bromide (11g, 0.071mol) were dissolved in compound 1-ii (330.3g, 3.57mol), and nitrogen was introduced at room temperature for deoxygenation for 30min and then stirred at room temperature for 3 hours. Then a mixed solution of sodium hydroxide (28.56g, 0.714mol) and ethanol (30g) was slowly added dropwise at a rate of 0.5 drops / second, and the reaction was continued for 2 hours under this temperature condition until the reaction was completed. The reaction solution was distilled under reduced pressure to remove excess compound 1-ii and solvent, washed with deionized water, extracted, and recrystallized to obtain compound 1-iii (125.95g, yield: 90%, HPLC purity: 96%).

[0034] The synthetic route of compound 1-v is as follows:

[0035] In a three-necked flask equipped with a stirring paddle, a thermometer and a nitrogen protection device, compound 1-iii (125g, 0.319mol) and NH4SCN (145.6g, 1.91mol) were dissolved in a mixture of acetone (1L) and tetrahydrofuran (1L), and reacted at room temperature for 12 hours under nitrogen protection until the reaction was completed. The reaction solution was distilled under reduced pressure to remove the solvent, 300mL of water was added to quench the reaction, and then extracted with dichloromethane (3×200ml), the combined organic phase was washed twice with deionized water, dried over anhydrous sodium sulfate, and finally purified by column chromatography with petroleum ether: acetone = 1:4 to obtain a white powder compound 1-v (112.17g, yield: 82.8%, HPLC purity: 97%).

[0036] The synthetic route of compound 1-vi is as follows:

[0037] In a three-necked flask equipped with a stirring paddle, a thermometer and a nitrogen protection device, sodium hydrosulfide (22.2g, 0.396mol) was dissolved in methanol (100mL) and cooled to 0°C. Then hydrogen sulfide gas was slowly introduced into the solution for 5 minutes. Compound 1-v (112g, 0.264mol) chloroform / methanol (volume ratio of 1:2, 1.6L) solution was added to the solution within 10 minutes, and hydrogen sulfide gas was continuously introduced. The mixture was stirred at 0°C for another 30 minutes, and then stirred at room temperature for 2 hours. TLC showed that the raw material disappeared. The reaction mixture was poured into water (2L), then acidified to pH=3-5 with a small amount of sulfuric acid (1M), extracted with ethyl acetate (3×200mL), and the combined organic phase was washed once with saturated brine, dried over anhydrous sodium sulfate and concentrated to obtain white solid compound 1-vi (127.5g, yield 98%, HPLC: 99%).

[0038] Synthesis route of compound 1-viii:

[0039] In a three-necked flask equipped with a stirring paddle, a thermometer, a water separator and a reflux tube, compound 1-vi (127.5 g, 0.259 mol), compound 1-vii (39.4 g, 0.259 mol) and TsOH (0.00313 mol, 0.54 g) were dissolved in benzene (480 mL), and the mixture was refluxed and stirred for 24 hours. TLC showed that the raw material disappeared. After the reaction solution was cooled, the organic phase was washed once with a saturated NaHCO3 aqueous solution, dried over anhydrous sodium sulfate and concentrated, and finally purified by column chromatography to obtain the target product compound 1-viii (154.6 g, yield: 98%, HPLC purity: 97%).

[0040] Synthesis route of compound 1-:

[0041] In a three-necked flask equipped with a stirring paddle, compound 1-viii (154 g, 0.253 mol) and compound 1-ix (82 ml, 0.506 mol) were dissolved in dichloromethane (300 mL) solvent, and Et3N (77.4 mL, 0.56 mol) and 4-(N,N-dimethylamino)pyridine (0.185 g, 0.0015 mol) were slowly added under ice bath, and stirred at room temperature for 12 hours. TLC showed that the raw material disappeared. The reaction solution was diluted with dichloromethane (500 mL), the combined organic phase was washed twice with saturated saline solution, the organic layer was dried with anhydrous sodium sulfate and concentrated, and purified by column chromatography using n-hexane: ethyl acetate (7:1) eluent to obtain the oily target product 1 (158.36 g, yield: 84%, HPLC purity: 98%).

[0042] The chemical structure of compound 1 was tested, and the refractive index was measured to be 1.653. The NMR characterization results are as follows:

[0043] 1 HNMR (400MHz, DMSO) δ: 7.08 (d, 2H), 6.09 (dt, 4H), 6.27-6.13 (t, 4H), 3.69-3.44 (m, 6H), 3.23-2.62 (m, 10H), 2.34 (s, 6H).

[0044] Example 2 Preparation of Compound 2

[0045] The preparation method of this embodiment is similar to that of embodiment 1, except that in step 4, acrylic anhydride is used instead of raw material The obtained compound 2 has the structural formula:

[0046]

[0047] The chemical structure of compound 2 was tested, and the refractive index performance was measured to be 1.675. The NMR characterization results are as follows:

[0048] 1 HNMR(400MHz,DMSO)δ:7.10(d,2H), 6.92-6.09(dt,4H), 6.35-6.15(m,6H),

[0049] 3.77-3.44(m,6H),3.23-3.11(m,6H),2.88-2.62(m,4H).

[0050] Example 3 Preparation of Compound 3

[0051] The preparation method of this embodiment is similar to that of embodiment 1, except that the raw material in step 1 is Step 4: Acrylic anhydride replaces the raw material The obtained compound 3 has the structural formula:

[0052]

[0053] The chemical structure of compound 3 was tested, and the refractive index was measured to be 1.673. The NMR characterization results are as follows:

[0054] 1 HNMR(400MHz, DMSO)δ:7.28-7.16(d,8H),6.27-6.13(m,4H),3.77-3.44(m,6H),3.09-2.96(m,6H),2.88-2.62(m,4H),2.34(s,6H).

[0055] Example 4 Preparation of Compound 4

[0056] The preparation method of this embodiment is similar to that of embodiment 1, except that the raw material in step 1 is Step 4: Acrylic anhydride replaces the raw material The obtained compound 4 has the structural formula:

[0057]

[0058] The chemical structure of compound 4 was tested, and the refractive index was measured to be 1.676. The NMR characterization results are as follows:

[0059] 1 HNMR (400 MHz, DMSO) δ: 7.28-7.16 (d, 8H), 6.37-6.19 (m, 6H), 3.8 compound 1-3.49 (m, 6H), 3.1 compound 1-2.98 (m, 6H), 2.86-2.59 (m, 4H).

[0060] Example 5 Preparation of Compound 5

[0061] The preparation method of this embodiment is similar to that of embodiment 1, except that the raw material in step 1 is Step 4: Methacrylic anhydride raw material is The obtained compound 5 has the structural formula:

[0062]

[0063] The chemical structure of compound 5 was tested, and the refractive index was measured to be 1.669. The NMR characterization results are as follows:

[0064] 1HNMR(400MHz,DMSO)δ:6.27(t,2H),6.13(t,2H),3.76-3.42(m,6H),3.37-3.11(m,6H),3.33(s,4H),2.87-2.64(m,4H),2.36(s,6H).

[0065] Example 6 Preparation of Compound 6

[0066] The preparation method of this embodiment is similar to that of embodiment 1, except that the raw material in step 1 is Step 4: Methacrylic anhydride raw material is The obtained compound 6 has the structural formula:

[0067]

[0068] The chemical structure of compound 6 was tested, and the refractive index was measured to be 1.672. The NMR characterization results are as follows:

[0069] 1 HNMR (400MHz, DMSO) δ: 6.35-6.19(m,6H), 3.76-3.43(m,6H), 3.37-3.11(m,6H), 3.32(s,4H), 2.88-2.62(m,4H).

[0070] Example 7 Preparation of Compound 7

[0071] The preparation method of this embodiment is similar to that of embodiment 1, except that the raw material in step 1 is Step 4: Methacrylic anhydride raw material is The obtained compound 7 has the structural formula:

[0072]

[0073] The chemical structure of compound 7 was tested, and the refractive index was measured to be 1.676. The NMR characterization results are as follows:

[0074] 1 HNMR(400MHz,DMSO)δ:7.90(dd,2H),7.55(dd,2H),7.38-7.27(m,8H),7.08-7.01(m,4H), 6.27-6.13(dt,4H),3.76-3.45(m,6H),3.23-2.97(m,6H),2.89-2.63(m,4H),2.33(s,6H).

[0075] Example 8 Preparation of Compound 8

[0076] The preparation method of this embodiment is similar to that of embodiment 1, except that the raw material in step 1 is Step 4: Methacrylic anhydride raw material is The obtained compound 8 has the structural formula:

[0077]

[0078] The chemical structure of compound 8 was tested, and the refractive index was measured to be 1.679. The NMR characterization results are as follows:

[0079] 1 HNMR(400MHz,DMSO)δ:7.89(dd,2H),7.54(dd,2H),7.37-7.26(m,8H),7.08(d,4 H),6.35-6.15(m,6H),3.77-3.44(m,6H),3.22-2.98(m,6H),2.88-2.62(m,4H).

[0080] The refractive index of the above compounds is above 1.668, and they can be used to prepare high-refractive devices. They have a wide spectral range, high chemical stability, and good adjustability, making them have wide application potential in high-refractive lenses, optical fibers and other optical components, ultraviolet, visible and near-infrared optical devices, lasers and optical fiber sensors and other optical communication systems, chemical and biological sensors, photoresists, coatings and other different fields.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A novel high-sulfur-content photopolymerizable high-refractive monomer, characterized in that: The structural formula is as follows: in, R1 is selected from -H, -CH3, R2 is selected from 2. The method for preparing a monomer according to claim 1, characterized in that: The method comprises the following steps: (1) using SH-R2-SH thiol compound as raw material to react with epichlorohydrin to form an epoxy group compound, and then reacting with NH4SCN to undergo an episulfide reaction to obtain an episulfide group compound; (2) reacting the cyclic sulfide group compound with sodium hydrosulfide and hydrogen sulfide to obtain two dithiol group compounds; (3) reacting the product of step 2 with dihydroxydithiane to obtain a dithiolane methylthiol group compound; (4) the product of step 3 is substituted with (meth)acrylic anhydride under base catalysis to prepare a corresponding high refractive monomer; The reaction formula is as follows: 。 3. The method according to claim 2, characterized in that In the step 1, the molar ratio of the thiol compound with hydrogen connected to both ends of the R2 substituent to epichlorohydrin is 1:2-10; and the molar ratio of the epoxy group compound to NH4SCN in the episulfide reaction is 1:2-8.

4. The method according to claim 2, characterized in that The reaction temperature for forming the epoxy group compound in step 1 is -120°C, and the episulfide reaction temperature is room temperature.

5. The method according to claim 2, characterized in that In step 2, the molar ratio of the episulfide compound to sodium hydrosulfide and hydrogen sulfide is 1:1.5-3:2-5.

6. The method according to claim 2, characterized in that The reaction temperature in step 2 is 0-5°C.

7. The method according to claim 2, characterized in that In the step 3, the molar ratio of the product of step 2 to dihydroxydithiane is: 1:compound 1-2.

8. The method according to claim 2, characterized in that The reaction temperature in step 3 is from room temperature to reflux heating.

9. The method according to claim 2, characterized in that In step 4, the molar ratio of the product of step 3 to (methyl) acrylic anhydride is 1:2-3, the base is triethylamine or 4-(N,N-dimethylamino)pyridine, and the molar ratio of the product of step 3 to the base is 1:2-5.

10. The method according to claim 2, characterized in that The reaction temperature in step 4 is 15-100°C.

Citation Information

Patent Citations

  • Sulfur-containing high-refraction photocuring monomer

    CN117567430A

  • Acrylic esters compound and use thereof

    CN1462272A

  • Polymerizable thio(METH)acrylate compound

    JP2002030082A

  • Method, apparatus and system for providing local store reservation and waiting service

    KR1020250031683A

  • Process for production of sulfur compounds

    US6646104B1